Organic Matter and Total Nitrogen Lead to Different Microbial Community Structure in Sediments Between Lagoon and Surrounding Areas by Regulating Xenococcus Abundance - Chen, Yonggan; Zheng, Minjing; Qiu, Yue; Wang, Hong; Zhang, Haonan; Tao, Qiongren; Luo, Hongwei; Zhang, Zhenhua (Frontiers in Microbiology, 2022)
Coastal lagoon is an important productive ecosystem on the Earth. In this study, we compared microbial community in the sediments between lagoon and surrounding areas, and explored mechanism for the variation of microbial community. As a result, the sediment of surrounding area showed significantly higher organic matter and total nitrogen than that of the lagoon. The linear regression analysis revealed that organic matter and total nitrogen are positively correlated with Xenococcus. Bacterial and fungal PCoA1 showed significantly positive relationships with the relative abundance of Xenococcus, indicating that Xenococcus affects the bacterial and fungal community in the sediments of both the lagoon and surrounding area. ANOSIM analysis demonstrated that there were significant differences in bacterial and fungal community structure in the sediments between the lagoon and surrounding areas. Therefore, organic matter and total nitrogen affect the microbial community structure in the sediments of lagoon and surrounding areas by regulating the abundance of Xenococcus.